Method for preparing a catalyst comprising a nickel active phase and a nickel-copper alloy distributed in a shell

In selective hydrogenation reaction, the distribution of nickel is controlled by using porous alumina support and butanol treatment technology, so that it is distributed both on the outer periphery of the catalyst shell and at the inner core, and the alloy is combined with copper to form, which solves the problem of nickel distribution. The activity and selectivity problems caused by uniformity achieve efficient catalytic performance and low-cost production.

CN115551633BActive Publication Date: 2024-12-24IFP ENERGIES NOUVELLES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180038885.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-29
Filing Date
2021-05-18
Publication Date
2024-12-24
Estimated Expiration
2041-05-18

AI Technical Summary

Technical Problem

In the prior art In selective hydrogenation reaction, the activity and selectivity of nickel catalysts are affected by the uneven distribution of nickel, resulting in low reaction efficiency and a high nickel content required, which increases costs.

Method used

Using porous alumina carrier, the distribution of nickel is controlled through the butanol solution impregnation and maturation steps, so that nickel is distributed both on the outer peripheral shell of the carrier and at the inner core, and the NiCu alloy is formed by combining copper elements to reduce the use of nickel, and through specific The heat treatment steps improve the activity and selectivity of the catalyst.

Benefits of technology

The same or higher catalyst performance as traditional technology is achieved, and the amount of nickel used is reduced, the reaction efficiency is improved, the production cost is reduced, and the reduction treatment is carried out at a lower temperature, extending the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115551633B_ABST
    Figure CN115551633B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a catalyst containing nickel and copper, which comprises the following steps: - impregnating a porous carrier with a butanol solution having a volume of 0.2-0.8 times the total pore volume of the carrier; - ripening the impregnated porous carrier for 0.5-40 hours; - impregnating the ripened impregnated carrier with a solution containing a precursor of a nickel active phase; - impregnating the carrier with a solution containing a copper precursor and a nickel precursor.
Need to check novelty before this filing date? Find Prior Art

Description

Prior art

[0002] Monounsaturated organic compounds (such as ethylene and propylene) are the basis for the preparation of polymers, plastics and other chemicals with added value. These compounds are obtained from natural gas, naphtha or gas oil that has been treated by steam cracking or catalytic cracking methods. These methods are carried out at high temperatures and, in addition to the desired monounsaturated compounds, also produce polyunsaturated organic compounds, such as acetylene, propadiene and methylacetylene (or propyne), 1,2-butadiene and 1,3-butadiene, vinylacetylene and ethylacetylene and other polyunsaturated compounds with boiling points equivalent to C5+ gasoline fractions (gasoline containing hydrocarbon compounds with 5 or more carbon atoms), especially styrene or indenes. These polyunsaturated compounds are highly reactive and lead to side reactions in the polymerization unit. It is therefore necessary to remove these polyunsaturated compounds before the economical use of these fractions. Selective hydrogenation is the main treatment method developed to remove unwanted polyunsaturated compounds from these hydrocarbon feedstocks in a targeted manner. It can convert polyunsaturated compounds into corresponding olefins or aromatic compounds while avoiding their complete saturation and the formation of corresponding alkanes or cycloalkanes.

[0003] Selective hydrogenation catalysts are usually based on metals from Group VIII of the Periodic Table of the Elements, preferably palladium or nickel. The metal is provided in the form of metal particles deposited on a support. The metal content, the size of the metal particles and the distribution of the active phase in the support are parameters that have an influence on the activity and selectivity of the catalyst.

[0004] The macroscopic distribution of metal particles in the support constitutes an important parameter, mainly in the context of rapid and sequential reactions, such as selective hydrogenation. It is usually desirable for these elements to be located in a shell at the periphery of the support, thus avoiding problems with intraparticle material transfer that could lead to activity defects and selectivity losses. Such catalysts are also known as "eggshell" catalysts.

[0005] Such catalysts are well known in the case of selective hydrogenation catalysts based on palladium. In fact, by means of a low palladium content (generally less than 1% by weight (1 wt%) of palladium relative to the catalyst) and a suitable preparation method, a thin palladium shell can be obtained at the periphery of the support particles (FR2922784, US2010 / 217052).

[0006] It is often suggested to replace palladium with nickel, which is a metal that is less active than palladium, which therefore requires adding more nickel to the catalyst. Therefore, nickel-based catalysts generally have a nickel metal content of 5% to 50% by weight relative to the catalyst. In these catalysts, the nickel is generally evenly distributed in the carrier. A possible approach to improve these catalysts in terms of activity and selectivity is to control the distribution of nickel in the carrier by depositing nickel on the shell at the periphery of the carrier in a more concentrated manner. Such catalysts are known in the prior art.

[0007] Document US 4 519 951 describes an "eggshell" catalyst with nickel on a porous support having a pore volume of at least 0.2 ml / g for pores smaller than 11.7 nm and at least 0.1 ml / g for pores larger than 11.7 nm. More than 50% by weight of the nickel is present in the shell, the thickness of which is equal to 0.15 times the radius of the support. This catalyst is used for the hydrogenation of fats.

[0008] Document CN101890351 describes a supported nickel catalyst in which more than 90% by weight of nickel is present in a shell 700 μm thick. The catalyst is prepared by dissolving a nickel salt in an ammonia-containing solution. These catalysts are used in selective hydrogenation applications.

[0009] Document US2012 / 0065442 describes a supported nickel catalyst, in which nickel is distributed both on a shell having a thickness of 3% to 15% of the diameter and on the core, and the nickel concentration ratio of the shell to the core is 3.0:1 to 1.3:1. The nickel active phase is deposited by spraying an ammonia solution of a nickel salt on the support.

[0010] The French patent application filed by the Applicant under No. 19 / 08.719 describes a method for preparing a nickel-based catalyst on an alumina support obtained according to a very specific method, the nickel being distributed both in a shell at the periphery of the support and in the inner core of the support, the thickness of said shell being between 2% and 15% of the diameter of the catalyst. The method for preparing such a catalyst requires firstly the use of a specific alumina support which has been subjected to a hydrothermal treatment in the presence of an acid solution and secondly the implementation of a hydrothermal treatment step after the addition of a specific organic additive to the catalyst precursor.

[0011] Subject matter of the invention

[0012] The present invention therefore relates to a novel process for preparing a catalyst which makes it possible to obtain a catalyst having performance qualities at least as good as those of the prior art, or even better, in terms of activity and selectivity, in the context of the selective hydrogenation of polyunsaturated compounds or of the hydrogenation of aromatic compounds, while using an effective amount of nickel phase (i.e. the amount of nickel ultimately located in the shell at the periphery of the support which allows the selective hydrogenation or the hydrogenation of aromatic compounds to proceed) which is lower than the amounts usually used in the prior art, in particular due to a better distribution of the nickel active phase in the support, which makes it more accessible to the reactants.

[0013] A subject of the present invention is a method for preparing a catalyst comprising nickel and copper and a porous alumina carrier, the proportion of nickel element relative to the total weight of the catalyst being 1% to 50% by weight, the proportion of copper element relative to the total weight of the catalyst being 0.5% to 15% by weight, the nickel being distributed both on a shell at the periphery of the carrier and in the core of the carrier, the thickness of the shell being 2% to 15% of the diameter of the catalyst, the size of the nickel particles in the catalyst measured in oxide form being 7nm to 25nm, the method comprising the following steps:

[0014] a) impregnating the support with a butanol solution having a volume V1 of 0.2 to 0.8 times the total pore volume TPV of the porous support to obtain an impregnated support;

[0015] b) maturing the impregnated porous support obtained at the end of step a) for 0.5 to 40 hours;

[0016] c) Carry out the following sub-steps in sequence:

[0017] c1) impregnating the aged impregnated porous support obtained at the end of step b) or the catalyst precursor obtained at the end of step d) with a solution comprising at least one precursor of a nickel active phase;

[0018] c2) optionally, drying the catalyst precursor obtained at the end of step c1) at a temperature below 250° C.;

[0019] d) Carry out the following sub-steps in sequence:

[0020] d1) impregnating the porous support, or the aged impregnated porous support obtained at the end of step b), or the catalyst precursor obtained at the end of step c), with at least one solution comprising at least one copper precursor and at least one nickel precursor at the desired copper concentration, so as to obtain on the final catalyst a copper content of 0.5% to 15% by weight relative to the total weight of the final catalyst;

[0021] d2) optionally, drying the catalyst precursor obtained at the end of step d1) at a temperature below 250° C.;

[0022] The step d) is performed before the step a), or between the step b) and the step c), or after the step c), which is understood as:

[0023] i) when step d) is performed before step a), sub-steps c2) and d2) are mandatory;

[0024] ii) when step d) is performed between step b) and step c), then sub-step c2) is mandatory;

[0025] iii) When step d) is performed after step c), then sub-step d2) is mandatory.

[0026] Surprisingly, the applicant has found that, regardless of the source of the porous alumina support, a specific step of impregnating a butanol solution on the porous alumina support, followed by a aging step before the step of adding the precursor of the nickel active phase to the aging impregnated support, and without an intermediate drying step between the impregnation of the butanol and the impregnation of the precursor of the nickel active phase, a catalyst can be obtained in which at least a portion of the nickel is distributed on the shell at the periphery of the support and another portion of the nickel is distributed in the core of the catalyst. Without wishing to be bound by any theory, the presence of butanol limits the migration of the nickel active phase to the core of the support. This is because only a portion of the pores are occupied by butanol. The aging step allows the butanol solution to migrate to the core of the support and releases a "free pore ring" accessible to nickel at the periphery of the support during the impregnation step of the active phase precursor. In addition, due to the poor miscibility of butanol and water, the butanol layer constitutes a barrier that limits the diffusion of nickel to the core of the support. Furthermore, the presence of the NiCu alloy on the catalysts enables these catalysts to be reduced in situ in the reactor prior to hydrogenation and at very low temperatures compared to conventional reduction temperatures, which occur ex situ and thus require an additional passivation step.

[0027] Preferably, the process further comprises a step e) in which the catalyst precursor obtained at the end of the sequence of steps a) to d) is reduced by contacting said catalyst precursor with a reducing gas at a temperature greater than or equal to 150°C and less than 250°C.

[0028] Preferably, step b) is carried out at a temperature lower than or equal to 60°C.

[0029] Preferably, in step a), an n-butanol solution is used.

[0030] In one embodiment according to the invention, when step d) is carried out before step a), the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) is preferably such that V2 = TPV - V1.

[0031] In one embodiment according to the present invention, wherein step d) is carried out between step b) and step c), or after step c), the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) and the volume V3 of the solution comprising the nickel precursor and the copper precursor provided in step d1) are such that V2+V3=TPV-V1.

[0032] Preferably, the copper precursor is selected from copper acetate, copper acetylacetonate, copper nitrate, copper sulfate, copper chloride, copper bromide, copper iodide or copper fluoride.

[0033] Preferably, the precursor of the nickel active phase is nickel nitrate, nickel chloride, nickel acetate or basic nickel carbonate.

[0034] In one embodiment according to the invention, the process further comprises a step c2') of calcining at a temperature ranging from 250°C to 600°C the dried catalyst precursor obtained at the end of step c2).

[0035] Preferably, in step a), the volume V1 of the butanol solution is 0.25-0.75 times the total pore volume TPV of the support.

[0036] Preferably, sub-step c2) and / or sub-step d2) is performed for a period of 0.5 hours to 12 hours.

[0037] A further subject matter according to the invention relates to a catalyst obtainable by the process according to the invention.

[0038] Another subject of the invention relates to a process for the selective hydrogenation of polyunsaturated compounds containing at least 2 carbon atoms per molecule contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 300° C., said process being carried out in the presence of a catalyst according to the invention or a catalyst obtained according to the process for preparation according to the invention, at a temperature ranging from 0° C. to 300° C., at a pressure ranging from 0.1 MPa to 10 MPa, when said process is carried out in the liquid phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio ranging from 0.1 to 10 and at a pressure ranging from 0.1 MPa to 10 MPa. -1 -200h -1 or, when the process is carried out in the gas phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio of 0.5 to 1000 and a 100 h / s space velocity. -1 -40000h -1 It is implemented at a time and space speed of.

[0039] Another subject of the invention relates to a process for hydrogenating at least one aromatic or polyaromatic compound contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 650° C., said process being carried out in the presence of a catalyst according to the invention or a catalyst obtained by the process for preparation according to the invention, in the gaseous or liquid phase, at a temperature ranging from 30° C. to 350° C., a pressure ranging from 0.1 MPa to 20 MPa, a hydrogen / (aromatic compound to be hydrogenated) molar ratio ranging from 0.1 to 10 and a reaction temperature ranging from 0.05 h / min. -1 -50h -1 It is implemented at a time and space speed of. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is a graph showing the distribution of nickel in the catalyst. The x-axis corresponds to the thickness of the catalyst, measured from the edge of the catalyst (in µm). The y-axis corresponds to the nickel density (in grams of nickel / mm 3 The nickel is distributed both on the outer shell of the carrier with a thickness of ep1 and in the core of the carrier. The nickel density on the shell is d 壳体 Greater than the nickel density d in the carrier core 内核 The thickness of the transition zone between the core and shell of the catalyst is denoted as ep2-ep1. DETAILED DESCRIPTION OF THE INVENTION

[0042] 1. Definition

[0043] In the text below, the groups of chemical elements are given according to the CAS classification (CRC Handbook of Chemistry and Physics, published by CRC Press, ed. DRLide, 81st edition, 2000-2001). For example, group VIII according to the CAS classification corresponds to the metals of columns 8, 9 and 10 according to the new IUPAC classification.

[0044] In this specification, according to the convention of IUPAC, "micropores" are understood to refer to pores with a diameter less than 2 nm (i.e. 0.002 µm); "mesopores" are understood to refer to pores with a diameter greater than 2 nm (i.e. 0.002 µm) and less than 50 nm (i.e. 0.05 µm), and "macroporos" are understood to refer to pores with a diameter greater than 50 nm (i.e. 0.05 µm).

[0045] In order to analyze the distribution of the metal phase on the support, the shell thickness is measured by Castaing microprobe (or electron microprobe microanalysis). The equipment used is CAMECA XS100, which is equipped with four crystal monochromators that can analyze four elements simultaneously. The Castaing microprobe analysis technique includes detecting the X-rays emitted by the solid after the elements of the solid are excited by a high-energy electron beam. In order to achieve such characterization, the catalyst particles are coated in epoxy resin blocks. These blocks are polished until a cross-section through the diameter of the beads or extrudates is obtained, and then metallized by depositing carbon in a metal evaporator. The electron probe is scanned along the diameter of five beads or extrudates to obtain the average distribution curve of the constituent elements of the solid. This method is well known to those skilled in the art and is defined in the publication "Measurement of palladium crust thickness on catalyst by EPMA" Materials Science and Engineering 32 (2012) by L. Sorbier et al. It can establish a distribution curve of a given element (nickel in this article) within the particle. In addition, the nickel concentration is defined for each measurement and thus for each analysis step. Therefore, the Ni density within the particle is defined as per mm 3 Ni concentration.

[0046] According to ASTM D4284-92, at a wetting angle of 140°, for example using Micromeritics ™ The brand model is Autopore III ™ The total pore volume was measured by mercury porosimetry using an apparatus.

[0047] The BET specific surface area is measured by a nitrogen physical adsorption method according to ASTM D3663-03 standard (the method described in the book "Adsorption by Powders & Porous Solids: Principles, Methodology and Applications" by Rouquerol F., Rouquerol J. and Singh K., Academic Press, 1999).

[0048] The median mesopore diameter is also defined as the diameter such that, among the combined pores making up the mesopore volume, all pores with a size less than this diameter account for 50% of the total mesopore volume as determined by mercury porosimetry.

[0049] The term "size of the nickel particles" is understood to mean the diameter of the nickel crystallites in the oxide form. The diameter of the nickel crystallites in the oxide form is determined by X-ray diffraction using the Scherrer equation from the width of the diffraction line at an angle 2θ = 43° (i.e. along the crystal direction

[200] ). This method is used in X-ray diffraction on polycrystalline samples or powders, which relates the full width at half height of the diffraction peak to the size of the particles, and is described in detail in the following reference: Appl. Cryst. (1978), 11, 102-113, "Scherrer after sixty years: A survey and some new results in the determination of crystallite size", JI Langford and AJC Wilson.

[0050] The nickel and copper contents were measured by X-ray fluorescence.

[0051] 2. Method for preparing catalyst

[0052] The steps of the preparation method are described in detail below.

[0053] Step a)

[0054] According to step a) of the method, the support is impregnated with a butanol solution having a volume V1 of 0.2-0.8 times, preferably 0.25-0.75 times, the total pore volume (also referred to herein as TPV) of the alumina support to be impregnated.

[0055] Butanol is understood to mean the alcohol corresponding to the empirical formula C4H 10 O is an organic compound comprising an alcohol functional group. Thus, butanol is understood to mean the family of organic compounds: butan-1-ol (or n-butanol), butan-2-ol, isobutanol and tert-butanol. Preferably, step a) is carried out in the presence of butan-1-ol.

[0056] Step b)

[0057] After step a), the impregnated support is aged in a wet state for 0.5 to 40 hours, preferably 1 to 30 hours. The maturation step b) is preferably carried out at a temperature lower than or equal to 60° C., more preferably at ambient temperature. This step allows the butanol solution to migrate to the inner core of the support.

[0058] Step c)

[0059] Step c1)

[0060] During step c1) of the process, the aged impregnated porous alumina support obtained at the end of step b) is impregnated with a solution comprising at least one precursor of a nickel active phase, so as to obtain a catalyst precursor. The impregnation step can be carried out according to methods known to those skilled in the art.

[0061] The pH of the solution comprising at least one precursor of the impregnated nickel active phase can be varied by the optional addition of an acid or a base.

[0062] Preferably, the nickel precursor is introduced in the form of an aqueous solution, for example in the form of a nitrate, carbonate, acetate, chloride or oxalate, in the form of a complex formed with a polyacid or an alcoholic acid and its salts, in the form of a complex formed with acetylacetonate, or in the form of any other inorganic derivative soluble in aqueous solution, and the nickel precursor is brought into contact with the support. Preferably, nickel nitrate, nickel chloride, nickel acetate or basic nickel carbonate are advantageously used as nickel precursor. Very preferably, the nickel precursor is nickel nitrate.

[0063] The nickel concentration in the solution is adjusted according to the pore volume of the support still available so as to obtain, for the supported catalyst, a nickel content of 1% to 50% by weight, more preferably 2% to 40% by weight, even more preferably 3% to 35% by weight, even more preferably 5% to 25% by weight of elemental nickel relative to the total weight of the catalyst.

[0064] Step c2)

[0065] In one embodiment according to the invention, a step c2 of drying the catalyst precursor obtained at the end of step c1) is carried out. The drying step c2) is advantageously carried out at a temperature below 250°C, preferably between 15°C and 180°C, more preferably between 30°C and 160°C, even more preferably between 50°C and 150°C, even more preferably between 70°C and 140°C, for a period of typically between 0.5 and 12 hours, even more preferably between 0.5 and 5 hours. Longer times are not excluded, but do not necessarily provide any improvement.

[0066] The drying step can be carried out by any technique known to those skilled in the art. It is advantageously carried out under an inert atmosphere or under an oxygen-containing atmosphere or under a mixture of an inert gas and oxygen. It is advantageously carried out under atmospheric pressure or under reduced pressure. Preferably, this step is carried out under atmospheric pressure, in the presence of air or nitrogen.

[0067] When step d) is carried out before step a) or between step b) and step c), step c2) is not optional. In these cases, at the end of step c2), the total or partial presence or absence of a butanol solution in the catalyst has no effect on the activity and / or selectivity of the catalyst in the context of the selective hydrogenation of polyunsaturated compounds or the hydrogenation of aromatic compounds.

[0068] Step c2′)

[0069] In one embodiment according to the invention, a step c2′) of calcining the dried catalyst precursor obtained at the end of step c2) is carried out at a temperature of 250° C. to 600° C. The calcination step c2′) can be carried out at a temperature of 250° C. to 600° C., preferably 350° C. to 550° C., for typically 0.5 to 24 hours, preferably 0.5 to 12 hours, even more preferably 0.5 to 10 hours, preferably under an inert atmosphere or an oxygen-containing atmosphere. Longer times are not excluded, but do not necessarily provide any improvement.

[0070] The total or partial presence or absence of a butanol solution in the catalyst has no influence on the activity and / or selectivity of the catalyst in the context of the selective hydrogenation of polyunsaturated compounds or of the hydrogenation of aromatic compounds at the end of step c2′).

[0071] Step d)

[0072] Step d1)

[0073] During step d1) of the process, the porous support, or the aged impregnated porous support obtained at the end of step b), or the catalyst precursor obtained at the end of step c), is impregnated with at least one solution comprising at least one copper precursor and at least one nickel precursor at the desired copper concentration, so as to obtain on the final catalyst a copper element content ranging from 0.5% to 15% by weight relative to the total weight of the final catalyst.

[0074] The pH of the solution comprising at least one impregnated nickel precursor and at least one impregnated copper precursor may be altered by the optional addition of an acid or a base.

[0075] Preferably, the nickel precursor and the copper precursor are introduced into an aqueous solution.

[0076] When the nickel precursor is introduced into the aqueous solution, it is advantageous to use a nickel precursor in the form of a nitrate, carbonate, acetate, chloride, hydroxide, basic carbonate, oxalate, sulfate or formates, in the form of a complex formed by a polyacid or an acid alcohol and its salt, in the form of a complex formed with acetylacetonate, in the form of a tetraamine or hexamine complex, or in the form of any other inorganic derivative soluble in aqueous solution, so that the nickel precursor is contacted with the catalyst precursor. Preferably, nickel nitrate, nickel hydroxide, nickel carbonate, nickel chloride or basic nickel carbonate are advantageously used as nickel precursor. Very preferably, the nickel precursor is nickel nitrate, nickel carbonate or nickel hydroxide.

[0077] When the copper precursor is introduced into the aqueous solution, it is advantageous to use a copper precursor in inorganic or organic form. In inorganic form, the copper precursor may be selected from copper acetate, copper acetylacetonate, copper nitrate, copper sulfate, copper chloride, copper bromide, copper iodide or copper fluoride. Very preferably, the copper precursor salt is copper nitrate.

[0078] Preferably, the nickel precursor is provided in step d1) in the desired concentration to obtain on the final catalyst (i.e. obtained at the end of reduction step e)) a nickel content in the nickel-copper alloy of 0.5% to 15% by weight, preferably 1% to 12% by weight, more preferably 1% to 10% by weight of nickel element relative to the total weight of the final catalyst.

[0079] The amount of the copper precursor or precursors introduced into the solution according to step d1) is chosen so as to provide a total copper content ranging from 0.5% to 15% by weight, preferably from 0.5% to 12% by weight, preferably from 0.75% to 10% by weight, even more preferably from 1% to 9% by weight of the copper element relative to the total weight of the final catalyst (i.e. obtained at the end of step e)).

[0080] Step d2)

[0081] In one embodiment according to the invention, a step d2) of drying the catalyst precursor obtained at the end of step d1) is carried out. Drying step d2) is advantageously carried out at a temperature below 250°C, preferably between 15°C and 180°C, more preferably between 30°C and 160°C, even more preferably between 50°C and 150°C, even more preferably between 70°C and 140°C, for a period of typically between 0.5 and 12 hours, even more preferably between 0.5 and 5 hours. Longer times are not excluded, but do not necessarily provide any improvement.

[0082] The drying step can be carried out by any technique known to those skilled in the art. It is advantageously carried out under an inert atmosphere or under an oxygen-containing atmosphere or under a mixture of an inert gas and oxygen. It is advantageously carried out under atmospheric pressure or under reduced pressure. Preferably, this step is carried out under atmospheric pressure, in the presence of air or nitrogen.

[0083] When step d) is carried out before step a) or after step c), sub-step d2) is not optional. When step d) is carried out after step c), then at the end of sub-step d2), the total or partial presence or absence of a butanol solution in the catalyst has no effect on the activity and / or selectivity of the catalyst in the context of the selective hydrogenation of polyunsaturated compounds or the hydrogenation of aromatic compounds.

[0084] Step d2′)

[0085] In one embodiment according to the invention, a step d2′) of calcining the dried catalyst precursor obtained at the end of step d2) is carried out at a temperature of 250° C. to 600° C. The calcination step d2′) can be carried out at a temperature of 250° C. to 600° C., preferably 350° C. to 550° C., for typically 0.5 to 24 hours, preferably 0.5 to 12 hours, even more preferably 0.5 to 10 hours, preferably under an inert atmosphere or an oxygen-containing atmosphere. Longer times are not excluded, but do not necessarily provide any improvement.

[0086] Execution of step c) and step d)

[0087] The method for preparing the catalyst comprises several embodiments. They are distinguished significantly by the order of introduction of the solution comprising the precursor of the nickel active phase and of the solution based on nickel and copper for obtaining the NiCu alloy.

[0088] Step d) may be performed before step a), between step b) and step c), or after step c) of the preparation method.

[0089] When step d) is carried out before step a), sub-steps c2) and d2) are mandatory. Preferably, step c2′) and / or step d2′) are also carried out. In this case, the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) is preferably such that V2=TPV−V1.

[0090] Sub-step c2) is mandatory when step d) is carried out between step b) and step c). Sub-step d2) is mandatory when step d) is carried out after step c). For both cases, preferably, the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) and the volume V3 of the solution based on nickel and copper provided in step d1) are such that V2+V3=TPV−V1.

[0091] In one embodiment according to the present invention, step d) is performed before step a).

[0092] In another embodiment according to the present invention, step d) is performed after step c).

[0093] The nickel-copper alloy present at least partially in reduced form makes it possible to reduce the nickel active phase using operating conditions less severe than those of the prior art, making it possible to carry out the reduction step directly in the reactor in which the hydrogenation of unsaturated compounds or aromatic compounds is desired.

[0094] Furthermore, the presence of copper in the catalyst makes it possible to maintain a good activity of the catalyst and a good service life of the catalyst when the catalyst is in contact with a hydrocarbon feedstock containing sulfur. In fact, the copper present in the catalyst is more likely to capture sulfur compounds contained in the feedstock than nickel, which limits the irreversible poisoning of the active sites.

[0095] Step e) Reduction by reducing gas (optional)

[0096] In one embodiment according to the invention, before using the catalyst in a catalytic reactor and implementing the hydrogenation process, a reduction treatment step e) is carried out in the presence of a reducing gas, so as to obtain a catalyst comprising nickel at least partially in metallic form. This step is advantageously carried out in situ, that is to say, after the catalyst is loaded into the hydrogenation reactor. This treatment makes it possible to activate the catalyst and form metal particles, in particular nickel in the zero-valent state. The in situ implementation of the catalyst reduction treatment makes it possible to omit the additional step of passivation of the catalyst with oxygen-containing compounds or CO2, which is necessary when the catalyst is prepared by implementing an ex situ reduction treatment (that is, outside the reactor for the hydrogenation of aromatic or polyaromatic compounds). In fact, when the reduction treatment is carried out ex situ, a passivation step must be carried out to maintain the metal phase of the catalyst in the presence of air (during the operation of transporting and loading the catalyst into the hydrogenation reactor), followed by a new step of reducing the catalyst.

[0097] The reducing gas is preferably hydrogen. The hydrogen can be used pure or as a mixture (e.g., hydrogen / nitrogen, hydrogen / argon, or hydrogen / methane mixtures). In the case where hydrogen is used as a mixture, any ratio can be envisioned.

[0098] According to one basic aspect of the preparation method of the present invention, the reduction treatment is carried out at a temperature higher than or equal to 150° C. and lower than 250° C., preferably 160° C.-230° C., more preferably 170° C.-220° C. The duration of the reduction treatment is 5 minutes to less than 5 hours, preferably 10 minutes to 4 hours, even more preferably 10 minutes to 110 minutes.

[0099] The temperature is usually raised to the desired reduction temperature slowly, for example, set at 0.1-10°C / min, preferably 0.3-7°C / min.

[0100] The hydrogen flow rate expressed in liters / hour / gram of catalyst precursor is 0.01-100 liters / hour / gram of catalyst precursor, preferably 0.05-10 liters / hour / gram of catalyst precursor, still more preferably 0.1-5 liters / hour / gram of catalyst precursor.

[0101] Step f) Passivation (optional)

[0102] The catalyst prepared according to the process of the invention may advantageously undergo a passivation step by means of a sulfur-containing compound, which can improve the selectivity of the catalyst and avoid thermal runaway during the start-up of the new catalyst. The passivation generally consists in irreversibly poisoning the most active sites of nickel present on the new catalyst by means of a sulfur-containing compound and thus in favor of its selective weakening of the activity of the catalyst. The passivation step is carried out using methods known to those skilled in the art.

[0103] The passivation step by means of a sulfur-containing compound is generally carried out at a temperature of 20° C. to 350° C., preferably 40° C. to 200° C., for 10 to 240 minutes. The sulfur-containing compound is, for example, selected from the following compounds: thiophene, tetrahydrothiophene, alkyl monosulfides, such as dimethyl sulfide, diethyl sulfide, dipropyl sulfide and propyl methyl sulfide, or an organic disulfide of formula HO-R1-SS-R2-OH, such as diethyl disulfide (commonly known as DEODS) of formula HO-C2H4-SS-C2H4-OH. The sulfur content is generally 0.1% to 2% by weight of said element relative to the total weight of the catalyst.

[0104] In one embodiment according to the invention, the preparation of the catalyst is carried out ex situ, that is to say before the catalyst is loaded into the reaction unit of the process for the selective hydrogenation or hydrogenation of aromatic compounds.

[0105] 3. Catalyst

[0106] According to the preparation method of the present invention, a catalyst containing nickel, copper and a porous alumina carrier can be obtained, wherein the proportion of nickel element relative to the total weight of the catalyst is 1% by weight to 50% by weight, and the proportion of copper element relative to the total weight of the catalyst is 0.5% by weight to 15% by weight. The nickel is distributed both on the shell at the periphery of the carrier and in the core of the carrier. The thickness of the shell is 2% to 15% of the diameter of the catalyst. The size of the nickel particles measured in the form of oxide in the catalyst is 7nm to 25nm.

[0107] Preferably, nickel is distributed both on the shell at the periphery of the carrier and in the core of the carrier, and the shell thickness ep1 is 2.5%-12% of the catalyst diameter, even more preferably 3%-10% of the catalyst diameter, and even more preferably 3%-7.5% of the catalyst diameter.

[0108] Preferably, the nickel density ratio between the shell and the core (also referred to herein as d 壳体 / d 内核 ) is strictly greater than 3, preferably greater than 3.5, preferably 3.8-15.

[0109] Preferably, the shell comprises more than 25 wt%, preferably more than 40 wt%, more preferably 45 wt%-90 wt%, even more preferably 60 wt%-90 wt% nickel element relative to the total weight of nickel contained in the catalyst.

[0110] Preferably, the molar ratio between nickel and copper is 0.5 mol / mol to 5 mol / mol, preferably 0.7 mol / mol to 4.5 mol / mol, more preferably 0.9 mol / mol to 4 mol / mol.

[0111] Preferably, at least a portion of the nickel and copper is in the form of a nickel-copper alloy, advantageously corresponding to the formula Ni x Cu y , where x is 0.1-0.9 and y is 0.1-0.9.

[0112] Preferably, the nickel content of the copper-nickel alloy is 0.5 wt % to 15 wt %, preferably 1 wt % to 12 wt %, more preferably 1 wt % to 10 wt % of nickel element relative to the total weight of the catalyst.

[0113] Preferably, the size of the nickel particles in the catalyst measured as oxide is from 7 nm to 25 nm, preferably from 8 nm to 23 nm.

[0114] Advantageously, the transition region between the core and the shell of the catalyst (also referred to herein as the core / shell transition region or according to Figure 1 The symbol in the figure is ep2-ep1), which is related to the change in nickel density along the catalyst thickness measured from the edge of the catalyst to the center of the catalyst, and is very abrupt. Preferably, the core / shell transition interval is 0.05%-3% of the catalyst diameter, preferably 0.5%-2.5% of the catalyst diameter.

[0115] The nickel content in the catalyst is advantageously between 1% and 50% by weight relative to the total weight of the catalyst, more preferably between 2% and 40% by weight, even more preferably between 3% and 35% by weight, and even more preferably between 5% and 25% by weight relative to the total weight of the catalyst.

[0116] The copper content is 0.5-15% by weight, preferably 0.5-12% by weight, preferably 0.75-10% by weight, even more preferably 1-9% by weight of copper element relative to the total weight of the catalyst.

[0117] The catalyst may be described as a "half eggshell" catalyst, wherein the concentration of nickel at the periphery of the support is higher than in the inner core of the support, where the nickel concentration is non-zero.

[0118] The specific surface area of ​​the catalyst is usually 10m 2 / g-350m 2 / g, preferably 25m 2 / g-300m 2 / g, more preferably 40m 2 / g-250m 2 / g.

[0119] The total pore volume of the catalyst is usually 0.1 ml / g to 1 ml / g, preferably 0.2 ml / g to 0.8 ml / g, particularly preferably 0.3 ml / g to 0.7 ml / g.

[0120] Preferably, the active phase of the catalyst contains no metals from group VIB. In particular, it contains no molybdenum or tungsten.

[0121] The catalyst (and the carrier for preparing the catalyst) is in the form of particles, and its diameter is advantageously 0.5mm-10mm. The particles can have any form known to those skilled in the art, such as beads (preferably 1mm-8mm in diameter), extrudates, sheets or hollow cylinders. Preferably, the catalyst (and the carrier for preparing the catalyst) is in the form of extrudates, and its diameter is 0.5mm-10mm, preferably 0.8mm-3.2mm, very preferably 1.0mm-2.5mm, and the length is 0.5mm-20mm. The "diameter" of the extrudate refers to the diameter of the circle enclosed in the cross section of these extrudates. The catalyst can advantageously be presented in the form of cylindrical, multi-lobed, trilobed or quadrilobed extrudates. Preferably, its shape is trilobed or quadrilobed. The shape of the blade can be adjusted according to all known methods in the prior art.

[0122] 4. Carrier

[0123] The properties of the aluminium oxide mentioned in this section correspond to the properties of the aluminium oxide before being subjected to step a) of the preparation process according to the invention.

[0124] The support is aluminum oxide, that is to say it contains at least 95% by weight, preferably at least 98% by weight, particularly preferably at least 99% by weight of aluminum oxide, relative to the weight of the support. The aluminum oxide generally has a crystalline structure of the delta, gamma or theta alumina type, either alone or as a mixture.

[0125] The alumina support may contain impurities, for example oxides of metals from Group IIA, Group IIIB, Group IVB, Group IIB, Group IIIA, Group IVA according to the CAS classification, preferably silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, magnesium oxide and calcium oxide, or alkali metals, preferably lithium, sodium or potassium, and / or alkaline earth metals, preferably magnesium, calcium, strontium or barium, or sulfur.

[0126] The specific surface area of ​​aluminum oxide is generally 10 m² / g to 400 m² / g, preferably 30 m² / g to 350 m² / g, and more preferably 50 m² / g to 300 m² / g.

[0127] The total pore volume of the alumina is generally from 0.1 ml / g to 1.2 ml / g, preferably from 0.3 ml / g to 0.9 ml / g, very preferably from 0.5 ml / g to 0.9 ml / g.

[0128] 5. Selective hydrogenation method

[0129] Another subject of the present invention is a process for the selective hydrogenation of polyunsaturated compounds containing at least 2 carbon atoms per molecule, such as dienes and / or alkynes and / or alkenyl aromatic compounds (also called styrenes), contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 300° C., said process being carried out in the presence of a catalyst obtained by the preparation process described above, at a temperature ranging from 0° C. to 300° C., at a pressure ranging from 0.1 MPa to 10 MPa, when said process is carried out in the liquid phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio ranging from 0.1 to 10 and at a pressure ranging from 0.1 MPa to 10 MPa. -1 -200h -1 or, when the process is carried out in the gas phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio of 0.5 to 1000 and a 100 h / s space velocity. -1 -40000h -1 It is implemented at a time and space speed of.

[0130] Monounsaturated organic compounds (such as ethylene and propylene) are the basis for the preparation of polymers, plastics and other chemicals with added value. These compounds are obtained from natural gas, naphtha or gas oil that has been treated by steam cracking or catalytic cracking methods. These methods are carried out at high temperatures and, in addition to the desired monounsaturated compounds, also produce polyunsaturated organic compounds, such as acetylene, propadiene and methylacetylene (or propyne), 1,2-butadiene and 1,3-butadiene, vinylacetylene and ethylacetylene and other polyunsaturated compounds with boiling points equivalent to the C5+ fraction (hydrocarbon compounds with at least 5 carbon atoms), in particular dienes or styrenes or indenes. These polyunsaturated compounds are highly reactive and lead to side reactions in the polymerization unit. It is therefore necessary to remove these polyunsaturated compounds before these fractions can be economically utilized.

[0131] Selective hydrogenation is the main treatment process developed for the targeted removal of undesirable polyunsaturated compounds from these hydrocarbon feedstocks. It enables the polyunsaturated compounds to be converted into the corresponding olefins or aromatics, while avoiding their complete saturation and thus the formation of the corresponding alkanes or cycloalkanes. In the case of steam cracked gasoline used as feedstock, selective hydrogenation can also selectively hydrogenate alkenyl aromatics to produce aromatic compounds, while avoiding hydrogenation of aromatic rings.

[0132] The hydrocarbon feedstock treated in the selective hydrogenation process has a final boiling point lower than or equal to 300° C. and contains at least 2 carbon atoms per molecule and comprises at least one polyunsaturated compound. The term “polyunsaturated compound” is intended to mean a compound comprising at least one acetylenic function and / or at least one diene function and / or at least one alkenyl aromatic function.

[0133] More specifically, the feedstock is selected from the group consisting of a steam cracked C2 fraction, a steam cracked C2-C3 fraction, a steam cracked C3 fraction, a steam cracked C4 fraction, a steam cracked C5 fraction and a steam cracked gasoline (also known as pyrolysis gasoline or C5+ fraction).

[0134] The steam cracked C2 fraction advantageously used for implementing the selective hydrogenation process according to the invention has, for example, the following composition: 40% to 95% by weight of ethylene, about 0.1% to 5% by weight of acetylene, the remainder being essentially ethane and methane. In some steam cracked C2 fractions, 0.1% to 1% by weight of C3 compounds may also be present.

[0135] The steam cracked C3 fraction advantageously used for carrying out the selective hydrogenation process according to the invention has, for example, the following average composition: about 90% by weight of propylene, about 1% to 8% by weight of propadiene and methylacetylene, the remainder being essentially propane. In some C3 fractions, 0.1% to 2% by weight of C2 compounds and C4 compounds may also be present.

[0136] The C2-C3 fraction can also be advantageously used for the selective hydrogenation process according to the invention. It has, for example, the following composition: about 0.1% to 5% by weight of acetylene, about 0.1% to 3% by weight of propadiene and methylacetylene, about 30% by weight of ethylene, about 5% by weight of propylene, the remainder being essentially methane, ethane and propane. The feedstock may also contain 0.1% to 2% by weight of C4 compounds.

[0137] The steam cracked C4 fraction advantageously used for carrying out the selective hydrogenation process according to the invention has, for example, the following average composition by weight: 1% by weight of butane, 46.5% by weight of butene, 51% by weight of butadiene, 1.3% by weight of vinylacetylene and 0.2% by weight of butyne. In some C4 fractions, 0.1% to 2% by weight of C3 compounds and C5 compounds may also be present.

[0138] The steam cracked C5 fraction advantageously used for carrying out the selective hydrogenation process according to the invention has, for example, the following composition: 21% by weight of pentane, 45% by weight of pentenes and 34% by weight of pentadienes.

[0139] The steam cracking gasoline or pyrolysis gasoline advantageously used for the implementation of the selective hydrogenation process according to the invention corresponds to a hydrocarbon fraction having a boiling point generally ranging from 0° C. to 300° C., preferably ranging from 10° C. to 250° C. The polyunsaturated hydrocarbons to be hydrogenated present in the steam cracking gasoline are in particular diolefin compounds (butadiene, isoprene, cyclopentadiene, etc.), styrenic compounds (styrene, α-methylstyrene, etc.) and indenic compounds (indene, etc.). Steam cracking gasoline generally contains a C5-C12 fraction and traces of C3, C4, C13, C14, C15 (for example, 0.1% to 3% by weight for each of these fractions). For example, the feedstock formed from pyrolysis gasoline generally has the following composition: 5-30% by weight of saturated compounds (paraffins and cycloalkanes), 40-80% by weight of aromatic compounds, 5-20% by weight of monoolefins, 5-40% by weight of diolefins, 1-20% by weight of alkenyl aromatic compounds, these compounds combined making up 100%. It also contains 0-1000 ppm by weight of sulfur, preferably 0-500 ppm by weight of sulfur.

[0140] Preferably, the polyunsaturated hydrocarbon feedstock treated according to the selective hydrogenation process of the present invention is a steam cracked C2 fraction, or a steam cracked C2-C3 fraction, or a steam cracked gasoline.

[0141] The selective hydrogenation process according to the present invention is intended to remove the polyunsaturated hydrocarbons present in the feedstock to be hydrogenated without hydrogenating monounsaturated hydrocarbons. For example, when the feedstock is a C2 fraction, the selective hydrogenation process is intended to selectively hydrogenate acetylene. When the feedstock is a C3 fraction, the selective hydrogenation process is intended to selectively hydrogenate propadiene and methylacetylene. In the case of a C4 fraction, the goal is to remove butadiene, vinyl acetylene (VAC) and butyne; in the case of a C5 fraction, the goal is to remove pentadiene. When the feedstock is steam cracking gasoline, the selective hydrogenation process is intended to selectively hydrogenate the polyunsaturated hydrocarbons present in the feedstock to be treated, thereby partially hydrogenating the diene compounds to produce monoolefins, and thereby partially hydrogenating the styrene compounds and indenes to produce the corresponding aromatic compounds, while avoiding the hydrogenation of aromatic rings.

[0142] The technical implementation of the selective hydrogenation method is implemented by, for example, injecting a polyunsaturated hydrocarbon feedstock and hydrogen upflow or downflow into at least one fixed bed reactor. The reactor can be isothermal or adiabatic. Adiabatic reactors are preferred. The polyunsaturated hydrocarbon feedstock can be advantageously diluted by one or more re-injections of the effluent obtained by the reactor in which the selective hydrogenation reaction occurs at various points of the reactor between the inlet and the outlet of the reactor to limit the temperature gradient in the reactor. The technical implementation of the selective hydrogenation method according to the present invention can also be advantageously implemented by loading at least the supported catalyst in a reactive distillation column or a reactor-exchanger or in a slurry-type reactor. The hydrogen stream can be introduced simultaneously with the feedstock to be hydrogenated and / or introduced at one or more different points in the reactor.

[0143] The selective hydrogenation of steam cracking C2 fraction, C2-C3 fraction, C3 fraction, C4 fraction, C5 fraction and C5+ fraction can be carried out in gas phase or liquid phase, preferably in liquid phase for C3 fraction, C4 fraction, C5 fraction and C5+ fraction, and preferably in gas phase for C2 fraction and C2-C3 fraction. Liquid phase reaction can reduce energy cost and extend the cycle time of catalyst.

[0144] Typically, the selective hydrogenation of a hydrocarbon feedstock containing polyunsaturated compounds containing at least 2 carbon atoms per molecule and having a final boiling point lower than or equal to 300° C. is carried out at a temperature of 0 to 300° C., a pressure of 0.1 MPa to 10 MPa, for a process carried out in the liquid phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio of 0.1 to 10 and a pressure of 0.1 MPa to 10 MPa. -1 -200h -1 The method is carried out at an hourly space velocity (defined as the ratio of the volume flow rate of the feed to the volume of the catalyst) of 0.5 to 1000, or, for a process carried out in the gas phase, at a hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio of 0.5 to 1000 and a 100 h / s ratio.-1 -40000h -1 It is implemented at a time and space speed of.

[0145] In one embodiment according to the present invention, when implementing a selective hydrogenation process in which the feedstock is a steam cracked gasoline containing polyunsaturated compounds, the (hydrogen) / (polyunsaturated compound to be hydrogenated) molar ratio is generally 0.5-10, preferably 0.7-5.0, more preferably 1.0-2.0, the temperature is 0°C-200°C, preferably 20°C-200°C, more preferably 30°C-180°C, the hourly space velocity (HSV) is generally 0.5h -1 -100h -1 , preferably 1h -1 -50h -1 The pressure is usually 0.3 MPa-8.0 MPa, preferably 1.0 MPa-7.0 MPa, and more preferably 1.5 MPa-4.0 MPa.

[0146] More preferably, the selective hydrogenation process is carried out in which the feedstock is a steam cracked gasoline containing polyunsaturated compounds, the hydrogen / (polyunsaturated compound to be hydrogenated) molar ratio is 0.7-5.0, the temperature is 20° C.-200° C., the hourly space velocity (HSV) is generally 1 h -1 -50h -1 , pressure is 1.0MPa -7.0MPa.

[0147] Still more preferably, a selective hydrogenation process is carried out in which the feedstock is a steam cracked gasoline containing polyunsaturated compounds, the hydrogen / (polyunsaturated compounds to be hydrogenated) molar ratio is 1.0-2.0, the temperature is 30° C.-180° C., the hourly space velocity (HSV) is generally 1 h -1 -50h -1 , pressure is 1.5MPa -4.0MPa.

[0148] The hydrogen flow rate is adjusted so as to have an amount sufficient to theoretically hydrogenate all the polyunsaturated compounds and to maintain an excess of hydrogen at the reactor outlet.

[0149] In another embodiment according to the invention, when a selective hydrogenation process is carried out in which the feedstock is a steam cracked C2 fraction and / or a steam cracked C2-C3 fraction containing polyunsaturated compounds, the (hydrogen) / (polyunsaturated compound to be hydrogenated) molar ratio is generally 0.5-1000, preferably 0.7-800, the temperature is 0° C.-300° C., preferably 15-280° C., the hourly space velocity (HSV) is generally 100 h -1 -40000h -1 , preferably 500h -1 -30000h -1The pressure is usually 0.1MPa-6.0MPa, preferably 0.2MPa-5.0MPa.

[0150] 6. Hydrogenation method of aromatic compounds

[0151] Another subject of the invention is a process for hydrogenating at least one aromatic or polyaromatic compound contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 650° C., generally ranging from 20° C. to 650° C., preferably ranging from 20° C. to 450° C. The hydrocarbon feedstock containing at least one aromatic or polyaromatic compound can be chosen from the following petroleum or petrochemical fractions: reformates from catalytic reforming, kerosene, light gas oils, heavy gas oils, cracked distillates, such as FCC recycle oils, coker unit gas oils or hydrocracked distillates.

[0152] The content of aromatic or polyaromatic compounds contained in the hydrocarbon feedstock treated in the hydrogenation process according to the invention is generally from 0.1% to 80% by weight, preferably from 1% to 50% by weight, particularly preferably from 2% to 35% by weight, the percentages being based on the total weight of the hydrocarbon feedstock. The aromatic compounds present in the hydrocarbon feedstock are, for example, benzene or alkylaromatic compounds, such as toluene, ethylbenzene, o-xylene, m-xylene or p-xylene, or aromatic compounds having several aromatic rings (polyaromatic compounds), such as naphthalene.

[0153] The sulfur or chlorine content in the raw material is usually less than 5000 ppm by weight, preferably less than 100 ppm by weight, particularly preferably less than 10 ppm by weight of sulfur or chlorine.

[0154] The technical implementation of the method for hydrogenating aromatic or polyaromatic compounds is implemented by, for example, injecting hydrocarbon feedstock and hydrogen upflow or downflow into at least one fixed bed reactor. The reactor may be of isothermal or adiabatic type. Adiabatic reactors are preferred. The hydrocarbon feedstock may advantageously be diluted by one or more reinjections of the effluent obtained from the reactor in which the hydrogenation reaction of aromatic compounds occurs at various points of the reactor located between the inlet and the outlet of the reactor to limit the temperature gradient in the reactor. The technical implementation of the method for hydrogenating aromatic compounds according to the present invention may also advantageously be implemented by loading at least the supported catalyst in a reactive distillation column or a reactor-exchanger or in a slurry-type reactor. The hydrogen stream may be introduced simultaneously with the feedstock to be hydrogenated and / or at one or more different points in the reactor.

[0155] The hydrogenation of aromatic or polyaromatic compounds can be carried out in the gas phase or in the liquid phase, preferably in the liquid phase. Typically, the hydrogenation of aromatic or polyaromatic compounds of a hydrocarbon feedstock containing aromatic or polyaromatic compounds and having a final boiling point lower than or equal to 650°C, typically 20°C-650°C, preferably 20°C-450°C, is carried out at a temperature of 30°C-350°C, preferably 50°C-325°C, at a pressure of 0.1 MPa-20 MPa, preferably 0.5 MPa-10 MPa, at a hydrogen / (aromatic compound to be hydrogenated) molar ratio of 0.1-10, at 0.05 h -1 -50h -1 , preferably 0.1h -1 -10h -1 The process is carried out at a space-time speed of .

[0156] The hydrogen flow rate is adjusted so as to have an amount sufficient to theoretically hydrogenate all the aromatic compounds and to maintain an excess of hydrogen at the reactor outlet.

[0157] The conversion of the aromatic or polyaromatic compounds is generally greater than 20 mol%, preferably greater than 40 mol%, more preferably greater than 80 mol%, and particularly preferably greater than 90 mol% of the aromatic or polyaromatic compounds contained in the hydrocarbon feedstock. The conversion is calculated by dividing the difference between the total number of moles of aromatic or polyaromatic compounds in the hydrocarbon feedstock and the total number of moles of aromatic or polyaromatic compounds in the product by the total number of moles of aromatic or polyaromatic compounds in the hydrocarbon feedstock.

[0158] According to a particular alternative form of the process according to the invention, a process for hydrogenating benzene in a hydrocarbon feedstock, for example a reformate produced by a catalytic reforming unit, is carried out. The benzene content in the hydrocarbon feedstock is generally 0.1% to 40% by weight, preferably 0.5% to 35% by weight, particularly preferably 2% to 30% by weight, the weight percentages being based on the total weight of the hydrocarbon feedstock.

[0159] The sulfur or chlorine content in the feedstock is generally less than 10 ppm by weight, preferably less than 2 ppm by weight, of sulfur or chlorine, respectively.

[0160] The hydrogenation of benzene contained in the hydrocarbon feedstock can be carried out in the gas phase or the liquid phase, preferably in the liquid phase. When it is carried out in the liquid phase, a solvent such as cyclohexane, heptane or octane may be present. Usually, the hydrogenation of benzene is carried out at a temperature of 30°C to 250°C, preferably 50°C to 200°C, more preferably 80°C to 180°C, at a pressure of 0.1 MPa to 10 MPa, preferably 0.5 MPa to 4 MPa, at a hydrogen / (benzene) molar ratio of 0.1 to 10, at 0.05 h -1 -50h -1 , preferably 0.5h -1 -10h -1 It is carried out at a time and space speed of .

[0161] The conversion rate of benzene is usually greater than 50 mol %, preferably greater than 80 mol %, more preferably greater than 90 mol %, particularly preferably greater than 98 mol %.

[0162] The invention will now be illustrated by the following examples, which are not limiting in any way. Example

[0163] For all catalysts mentioned in the examples below, the support was alumina A with a specific surface area of ​​80 m 2 / g, the pore volume is 0.7ml / g, and the median mesopore diameter is 12nm.

[0164] Example 1: Preparation of aqueous solution of Ni precursor

[0165] An aqueous solution (solution S1) of the Ni precursor used to prepare catalysts A to H was prepared by dissolving 43.5 g of nickel nitrate (NiNO3, supplier Strem Chemicals®) in a volume of 13 ml of distilled water. Solution S1 was obtained, and its nickel concentration was 350 g of Ni per liter of solution.

[0166] Example 2: Preparation of aqueous solution of NiCu alloy precursor

[0167] An aqueous solution of a precursor of a NiCu alloy for preparing a catalyst containing NiCu (solution S2) was prepared by dissolving 14.5 g of nickel nitrate (NiNO3, supplier Strem Chemicals®) in a volume of 13 ml of distilled water. A solution having a nickel concentration of 116.6 g of Ni per liter of solution was obtained. A copper nitrate precursor was then added to give a Ni / Cu molar ratio of 1.

[0168] Solution S2 is obtained. This makes it possible to introduce a precursor of a NiCu alloy whose Ni weight content relative to the final catalyst is 5% by weight relative to the total weight of the catalyst.

[0169] Example 3: Preparation of Catalyst A According to the Invention [10 wt % Ni + NiCu-pre-impregnation ButOH 25% TPV

[0170] 10 g of alumina were impregnated with 2.4 ml of butanol added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 7.1 ml of solution S1 were then dry-impregnated on the aged impregnated support obtained above by dropwise addition. The catalyst precursor obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 were dry-impregnated by dropwise addition. The solid thus obtained was then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0171] Catalyst A was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst A thus obtained are listed in Table 1 below.

[0172] Example 4: Preparation of Catalyst B According to the Invention [5 wt% Ni + NiCu-pre-impregnation ButOH 25% TPV

[0173] 10 g of alumina was impregnated with 2.4 ml of butanol added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 7.1 ml of a twice diluted solution S1 (3.55 ml of solution S1 was diluted with water to obtain 7.1 ml of a final solution, half the concentration of Example 3) was dry impregnated on the above-obtained aged impregnated support by dropwise addition. The catalyst precursor thus obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of the solution S2 prepared in Example 2 was dry impregnated by dropwise addition. The solid thus obtained was then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0174] Catalyst B was obtained, which contained 10 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst B thus obtained are listed in Table 1 below.

[0175] Example 5: Preparation of Catalyst C According to the Invention [10 wt% Ni + NiCu-Pre-impregnation ButOH 75% TPV

[0176] 10 g of alumina were impregnated with 7.2 ml of butanol added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 2.4 ml of solution S1 were then dry-impregnated on the aged impregnated support obtained above by dropwise addition. The catalyst precursor thus obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 were dry-impregnated by dropwise addition. The solid thus obtained was then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0177] Catalyst C was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst C thus obtained are listed in Table 1 below.

[0178] Example 6: Preparation of Catalyst D Not According to the Invention [Conventional Catalyst with NiCu, 10 wt. % Ni]

[0179] 10 ml of solution S1 were dry impregnated on the alumina support A by dropwise addition. The impregnated support thus obtained was subsequently dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 were dry impregnated by dropwise addition. The solid thus obtained was subsequently dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0180] Catalyst D was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst D thus obtained are listed in Table 1 below.

[0181] Example 7: Preparation of Catalyst E Not According to the Invention [ButOH Pre-impregnation in Eggshell, 10 wt.% Ni]

[0182] 10 g of alumina was impregnated with 2.4 ml of butanol added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 7.1 ml of the solution S1 prepared in Example 1 was dry-impregnated on the aged impregnated support obtained above by dropwise addition.

[0183] The catalyst precursor thus obtained was subsequently dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0184] Catalyst E was obtained, which contained 10% by weight of nickel element relative to the total weight of the catalyst. The properties of the catalyst E thus obtained are shown in Table 1 below.

[0185] Example 8: Preparation of Catalyst F Not According to the Invention [10 wt% Ni-Post-Impregnation ButOH 25% TPV +NiCu]

[0186] 7.1 ml of solution S1 was dry impregnated on alumina support A by dropwise addition. The catalyst precursor thus obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 was dry impregnated on the catalyst precursor obtained above by dropwise addition.

[0187] The solid thus obtained is then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours, under a dry air stream of 1 l / h / g catalyst. 2.4 ml of butanol are then impregnated. The solid is then aged at 60° C. for 30 minutes. The solid thus obtained is then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours, under a dry air stream of 1 l / h / g catalyst.

[0188] Catalyst F was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst F thus obtained are listed in Table 1 below.

[0189] Example 9: Preparation of Catalyst G Not According to the Invention [10 wt% Ni-prepreg in toluene 25% TPV, NiCu]

[0190] 10 g of alumina were impregnated with 2.4 ml of toluene added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 7.1 ml of solution S1 were then dry-impregnated on the aged impregnated support obtained above by dropwise addition. The catalyst precursor thus obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 was dry-impregnated by dropwise addition. The solid thus obtained was then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0191] Catalyst G was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst G thus obtained are listed in Table 1 below.

[0192] Example 10: Preparation of Catalyst H Not According to the Invention [10 wt. % Nickel-Prepreg in n-Propanol 25 wt. TPV, NiCu]

[0193] 10 g of aluminum oxide A was impregnated with 2.4 ml of n-propanol added dropwise. The impregnated support was then aged at 60° C. for 30 minutes. 7.1 ml of solution S1 was then dry-impregnated on the aged impregnated support obtained above by dropwise addition. The catalyst precursor thus obtained was then dried in an oven at 120° C. for 12 hours. Next, 10 ml of solution S2 prepared in Example 2 was dry-impregnated by dropwise addition. The solid thus obtained was then dried in an oven at 120° C. for 12 hours and then calcined at 450° C. for 2 hours under a dry air stream of 1 l / h / g catalyst.

[0194] Catalyst H was obtained, which contained 15 wt % of nickel element (including 5 wt % of nickel element in the NiCu alloy) relative to the total weight of the catalyst. The characteristics of the catalyst H thus obtained are listed in Table 1 below.

[0195] Example 11: Characterization

[0196] The amount of alloy obtained after the calcination step and then the reduction step is determined by X-ray diffraction (XRD) analysis on a sample of the catalyst in powder form.

[0197] The amount of nickel in metallic form obtained after the reduction step was determined by X-ray diffraction (XRD) analysis on a sample of the catalyst in powder form. Between the reduction step and the entire process of characterization by XRD, the catalyst was never returned to open air. The diffraction pattern was obtained by radioactive crystal analysis using a conventional powder method with copper Kα1 radiation (λ=1.5406Å) by means of a diffractometer.

[0198] The Ni concentrations located near 52° 2θ in all diffraction patterns of each catalyst sample analyzed were calculated. 0 The degree of reduction is then calculated by subtracting the signal (caused by alumina) present below the 52° line as soon as ambient temperature is reached from the area of ​​the line.

[0199] Table 2 below summarizes the reduction degree or nickel metal Ni characterized by XRD after all catalysts A to H were reduced at 170° C. for 90 minutes under a hydrogen stream. 0 The contents of Ni (expressed in wt. % relative to the total weight of "active" Ni not constituting an alloy) are also compared with the degree of reduction obtained for Catalyst E (nickel only) after a conventional reduction step, i.e. at a temperature of 400° C. for 15 hours under a stream of hydrogen.

[0200] At ambient temperature, delta and theta alumina as well as large CuO and NiO lines were detected on all copper- and nickel-containing catalysts after calcination.

[0201] In addition, the corresponding Ni 0.76 Cu 0.24 In the form of alloy wire.

[0202] In order to evaluate the degree of reduction and thus Ni 0 The formation of Ni near 52°2θ in all diffraction patterns was measured. 0 The area of ​​the line is determined by subtracting the signal (caused by alumina) that appears below the 52° line as soon as ambient temperature is reached. 0 The relative percentage of .

[0203] Table 2 below summarizes the degree of reduction or Ni of all catalysts characterized by XRD after reduction at 170°C for 90 minutes under a hydrogen stream. 0 These values ​​were also compared with the degree of reduction obtained for Catalyst E (nickel only) after a conventional reduction step, ie at a temperature of 400° C. under a hydrogen stream for 15 hours.

[0204] Table 1

[0205] catalyst Solvent (Volume % of TPV relative to carrier) Ni (wt%) Particle size (nm) Shell thickness / particle diameter (%) <![CDATA[D 壳体 / D 内核 ]]> Ni content in shell / total Ni (%) A (according to the present invention) 25% BuTOH in pre-preg 15 11.5 6.8 5 66 B (according to the present invention) 25% BuTOH in pre-preg 10 7 3.8 12 71 C (according to the present invention) 75% BuTOH in pre-preg 15 12 4.7 10 70 D (not according to the invention) - 15 12 Even distribution - - E (not according to the invention) 25% BuTOH in pre-preg 10 12 6.8 5 66 F (not according to the invention) 25% BuTOH in post-maceration 15 12 Even distribution - - G (not according to the invention) 25% toluene in pre-impregnation 15 11.5 Even distribution - - H (not according to the invention) 25% n-propanol in pre-dip 15 11.5 Even distribution - -

[0206] Table 2

[0207] catalyst Final restoration Ni / Cu Particle size (nm) <![CDATA[Only Ni after reduction 0 Percentage (%) (XRD)]]> A (according to the present invention) 170℃, 90min yes 11.5 90 B (according to the present invention) 170℃, 90min yes 7 92 C (according to the present invention) 170℃, 90min yes 12 90 D (not according to the invention) 170℃, 90min yes 12 90 E (not according to the invention) 170℃, 90min no 12 0* E (not according to the invention) 400℃, 15 hours no 12 80 F (not according to the invention) 170℃, 90min yes 12 90 G (not according to the invention) 170℃, 90min yes 12 95 H (not according to the invention) 170℃, 90min yes 12 95

[0208] *Nickel is in the form of NiO.

[0209] For Catalyst E (10% Ni / alumina only), the degree of nickel reduction was 0% after the exact same reduction treatment under hydrogen as Catalysts A, B, C, D, F, G, and H. It was necessary to reduce Catalyst E at 400°C to reduce the nickel oxide to Ni 0 The degree of reduction is about 80%.

[0210] Example 12: Catalytic Test: Selective Hydrogenation Performance of a Mixture Containing Styrene and Isoprene (A HYD1 )

[0211] Catalysts A to H described in the above examples were tested for the selective hydrogenation of a mixture containing styrene and isoprene.

[0212] The composition of the feedstock to be selectively hydrogenated is as follows: 8% by weight of styrene (supplier Sigma Aldrich®, purity 99%), 8% by weight of isoprene (supplier Sigma Aldrich®, purity 99%) and 84% by weight of n-heptane (solvent) (supplier VWR®, purity>99% Chromanorm HPLC). This composition corresponds to the initial composition of the reaction mixture. This mixture of model molecules represents pyrolysis gasoline.

[0213] The selective hydrogenation reaction was carried out in a 500 ml stainless steel autoclave equipped with a magnetically driven mechanical stirrer and capable of operating at a maximum pressure of 100 bar (10 MPa) and a temperature range of 5°C to 200°C.

[0214] 214ml of n-heptane (supplier VWR®, purity>99% Chromanorm HPLC) and 3ml of catalyst were added to the autoclave. The autoclave was closed and purged. The autoclave was then pressurized under 35 bar (3.5MPa) of hydrogen. First, at 170°C, under a hydrogen stream of 1 l / h / g, catalyst A to catalyst H were in-situ reduced for 90 minutes (temperature ramp of 1°C / minute) (this is equivalent to step e) of an embodiment of the preparation method according to the present invention). The autoclave was then brought to a test temperature, equal to 30°C. At time t = 0, a mixture of about 30g containing styrene, isoprene, n-heptane, pentamethylenethiol and thiophene was introduced into the autoclave. The reaction mixture then had the above composition and began to stir at 1600rpm. The pressure in the autoclave was kept constant at 35 bar (3.5MPa) using a gas tank located upstream of the reactor.

[0215] Another test was performed on Catalyst E, but the catalyst reduction temperature was 400°C for 16 hours.

[0216] The progress of the reaction is monitored by sampling the reaction medium at regular intervals: styrene is hydrogenated to produce ethylbenzene, while the aromatic rings are not hydrogenated, and isoprene is hydrogenated to produce methylbutene. If the reaction is prolonged beyond the necessary time, the methylbutene is in turn hydrogenated to produce isopentane. The consumption of hydrogen is also monitored over time by the decrease in pressure in a gas tank located upstream of the reactor. The catalytic activity is expressed in moles of H2 consumed per minute and per gram of Ni.

[0217] Table 3 below shows the catalytic activities (A HYD1 ). They were correlated with the catalytic activity measured for Catalyst E prepared under conventional reduction conditions (reduction at a temperature of 400° C. under a hydrogen stream for 16 hours).

[0218] Example 13: Catalytic test: Toluene hydrogenation performance (A HYD2 )

[0219] Catalysts A to H described in the above examples were also tested for the hydrogenation of toluene. The selective hydrogenation reaction was carried out in the same autoclave as described in Example 12.

[0220] 214 ml of n-heptane (supplier VWR®, purity> 99% Chromanorm HPLC) and 3 ml of catalyst were added to the autoclave. The autoclave was closed and purged. The autoclave was then pressurized under 35 bar (3.5 MPa) of hydrogen. First, at 170°C, under a hydrogen stream of 1 l / h / g, catalyst A to catalyst H were in-situ reduced for 90 minutes (temperature ramp of 1°C / min) (this corresponds to step e) of one embodiment of the preparation method according to the present invention). After adding 216 ml of n-heptane (supplier VWR®, purity> 99% Chromanorm HPLC), the autoclave was closed, purged, then pressurized under 35 bar (3.5 MPa) of hydrogen, and the autoclave was brought to the test temperature, equal to 80°C. At time t = 0, about 26 g of toluene (supplier SDS®, purity> 99.8%) were introduced into the autoclave (the initial composition of the reaction mixture was 6 wt % toluene / 94 wt % n-heptane), and stirring was started at 1600 rpm. The pressure in the autoclave was kept constant at 35 bar (3.5 MPa) using a gas tank located upstream of the reactor.

[0221] The progress of the reaction is monitored by sampling the reaction medium at regular time intervals: toluene is completely hydrogenated to produce methylcyclohexane. The consumption of hydrogen is also monitored over time by the decrease in pressure in a gas tank located upstream of the reactor. The catalytic activity is expressed in moles of H2 consumed per minute and per gram of Ni.

[0222] Table 3 below shows the catalytic activities (A HYD2 ). They were correlated with the catalytic activity measured for Catalyst E prepared under conventional reduction conditions (reduction at a temperature of 400° C. under a hydrogen stream for 16 hours).

[0223] Table 3

[0224] catalyst Reduction(℃) <![CDATA[Ni 0 Content (%)]]> <![CDATA[A HYD1 (%)]]> <![CDATA[A HYD2 (%)]]> A (according to the present invention) 170℃, 16 h 15 180 175 B (according to the present invention) 170℃, 16 h 10 150 152 C (according to the present invention) 170℃, 16 h 15 181 190 D (not according to the invention) 170℃, 16 h 15 60 70 E (not according to the invention) 170℃, 16 h 15 < 1 < 1 E (not according to the invention) 400℃, 16 h 15 100 100 F (not according to the invention) 170°C, 16 h 15 55 45 G (not according to the invention) 170℃, 16 h 15 93 102 H (not according to the invention) 170℃, 16 h 15 95 98

[0225] This clearly shows that the improved A of catalysts A, B and C obtained by the preparation method according to the invention compared to catalysts D to H not according to the invention. HYD1 and A HYD2 Performance. For Catalyst A, Catalyst B and Catalyst C, the nickel oxide was reduced to a level of 90% at 170°C and had particles distributed in a "half eggshell" shape. The method for preparing Catalyst D did not include the addition of n-butanol in the pre-impregnation, which had the effect of not distributing the nickel in a half eggshell shape. Catalyst E had lower activity due to conventional impregnation without pre-impregnation with butanol. Catalyst F was post-impregnated with butanol, which did not achieve an eggshell distribution of nickel. Catalyst G and Catalyst H were prepared by pre-impregnation steps with toluene and propanol, respectively. In both cases, the nickel was uniformly distributed throughout the catalyst particles. Therefore, for A HYD1 In terms of the catalysts, the activities of catalysts G and H are much lower than that of catalyst A. This can be explained by the “half-eggshell” distribution of nickel on catalysts A, B, and C, which significantly improves their activities, especially in fast hydrogenation reactions. The lower activity of catalyst E is due to the absence of NiCu, which cannot obtain reduced Ni at 170 °C, the active phase for hydrogenation.

Claims

1. A method for preparing a catalyst comprising nickel and copper and a porous alumina carrier, wherein the proportion of nickel element relative to the total weight of the catalyst is 1% to 50% by weight, the proportion of copper element relative to the total weight of the catalyst is 0.5% to 15% by weight, the nickel is distributed both on the shell at the periphery of the carrier and in the core of the carrier, the thickness of the shell is 2% to 15% of the diameter of the catalyst, and the size of the nickel particles in the catalyst measured in the form of oxide is 7nm to 25nm, the method comprising the following steps: a) impregnating the support or the catalyst precursor obtained at the end of step d) with a butanol solution having a volume V1 of 0.2 to 0.8 times the total pore volume TPV of the porous support, so as to obtain an impregnated support; b) ripening the impregnated porous support obtained at the end of step a) for 0.5 hours to 40 hours, wherein step b) is carried out at a temperature lower than or equal to 60° C.; c) Carry out the following sub-steps in sequence: c1) impregnating the aged porous support obtained at the end of step b) or the catalyst precursor obtained at the end of step d) with a solution comprising at least one precursor of a nickel active phase; c2) optionally, drying the catalyst precursor obtained at the end of step c1) at a temperature below 250° C.; d) Carry out the following sub-steps in sequence: d1) impregnating the porous support, or the aged porous support obtained at the end of step b), or the catalyst precursor obtained at the end of step c), with at least one solution comprising at least one copper precursor and at least one nickel precursor at the desired copper concentration, so as to obtain on the final catalyst a copper content of 0.5% to 15% by weight relative to the total weight of the final catalyst; d2) optionally, drying the catalyst precursor obtained at the end of step d1) at a temperature below 250° C.; The step d) is performed before the step a), or between the step b) and the step c), or after the step c), which is understood as: i) when step d) is performed before step a), sub-steps c2) and d2) are mandatory; ii) when step d) is performed between step b) and step c), then sub-step c2) is mandatory; iii) When step d) is performed after step c), then sub-step d2) is mandatory.

2. The process of claim 1, wherein in step a), an n-butanol solution is used.

3. The method according to any one of claims 1 to 2, wherein when step d) is carried out before step a), the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) is such that V2 = TPV - V1.

4. The method of any one of claims 1 to 2, wherein when step d) is performed between step b) and step c), or after step c), the volume V2 of the solution comprising at least one precursor of the nickel active phase provided in step c1) and the volume V3 of the solution comprising the nickel precursor and the copper precursor provided in step d1) are such that V2+V3=TPV-V1.

5. The method of any one of claims 1-2, wherein the copper precursor is selected from copper acetate, copper acetylacetonate, copper nitrate, copper sulfate, copper chloride, copper bromide, copper iodide or copper fluoride.

6. The method according to any one of claims 1 to 2, wherein the precursor of the nickel active phase is nickel nitrate, nickel chloride, nickel acetate or basic nickel carbonate.

7. The process according to any one of claims 1 to 2, further comprising a step c2') of calcining the dried catalyst precursor obtained at the end of step c2) at a temperature ranging from 250°C to 600°C.

8. The method according to any one of claims 1 to 2, wherein in step a), the volume V1 of the butanol solution is 0.25 to 0.75 times the total pore volume TPV of the support.

9. The method of any one of claims 1-2, wherein sub-step c2) and / or sub-step d2) is performed for a period of 0.5 to 12 hours.

10. The process according to any one of claims 1 to 2, further comprising a step e) in which the catalyst precursor obtained at the end of the sequence of steps a) to d) is reduced by contacting the catalyst precursor with a reducing gas at a temperature greater than or equal to 150° C. and less than 250° C.

11. A catalyst comprising nickel, copper and a porous alumina carrier, wherein the proportion of nickel element relative to the total weight of the catalyst is 1% to 50% by weight, the proportion of copper element relative to the total weight of the catalyst is 0.5% to 15% by weight, the nickel is distributed both on the shell at the periphery of the carrier and in the core of the carrier, the thickness of the shell is 2% to 15% of the diameter of the catalyst, the size of the nickel particles measured in the form of oxide in the catalyst is 7nm to 25nm, and the catalyst is obtained by the method as described in any one of claims 1 to 10.

12. A process for the selective hydrogenation of polyunsaturated compounds containing at least 2 carbon atoms per molecule contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 300° C., in the presence of a catalyst according to claim 11 or a catalyst obtained according to any one of claims 1 to 10, at a temperature of 0° C. to 300° C., a pressure of 0.1 MPa to 10 MPa, when the process is carried out in the liquid phase, at a molar ratio of hydrogen to the polyunsaturated compound to be hydrogenated of 0.1 to 10 and a pressure of 0.1 h / mol. -1 -200h -1 or, when the process is carried out in the gas phase, at a molar ratio of hydrogen to the polyunsaturated compound to be hydrogenated of 0.5 to 1000 and at a speed of 100 h -1 -40000h -1 It is implemented at a time and space speed of.

13. A process for hydrogenating at least one aromatic or polyaromatic compound contained in a hydrocarbon feedstock having a final boiling point lower than or equal to 650° C., in the presence of a catalyst according to claim 11 or a catalyst obtained according to any one of claims 1 to 10, in the gaseous or liquid phase, at a temperature of 30° C. to 350° C., a pressure of 0.1 MPa to 20 MPa, a molar ratio of hydrogen to the aromatic compound to be hydrogenated of 0.1 to 10 and a reaction temperature of 0.05 h / min. -1 -50h -1 It is implemented at a time and space speed of.